Using Video in The Tiktok Application to Improve Persuasus Text Writing Skills - Dhony Franciska; Dwi Rohman Soleh; Nunung Nurhidayati (Edukasi, 2023)
The purpose of this study is to use the TikTok application for video media to help students become more proficient in writing persuasive texts. The method used is a collective action method with a quantitative research type. The research subjects were 28 students of class VIII G. The data achieved is the result of persuasive writing skills synthesized by students by applying problem-based learning with the help of TikTok videos. The results of writing activities are persuasive. This research action was carried out in two cycles with two meetings. The results of the PBL model persuasive writing skills training with TikTok media were 67.6 and Cycle II 76.2. Acquisition results increased by 8.6, while the median score for pre-operative surgery was 55.3. This increase is due to students being able to follow. The learning process went well and was stable, their reading and writing skills had improved, but at the previous stage they still did not understand the structure and language of persuasive texts.Â  After applying models and media, students will more easily understand the text and be able to process words in writing persuasive texts.Â Â